Muslim-Friendly Tourism Towards Good Tourism Governance - Siti Hajar; Faustyna Faustyna; Kholilul Kholik (Department of Government Studies Universitas Muhammadiyah Makassar, 2022)
The oftenly issue that found in Toba Lake is the lack of facilities to support both foreign and domestic tourists. This convenience is related to culinary (food) availability in places of worship and hotels based on national standards. Since the majority visitors who come to Toba Lake are Muslims; thus it is very important to have a friendly-based tourism policy through good governance to create a superior tourist destination. This study aimed to determine the concept of policies to realize Muslim-friendly tourism toward Good Tourism Governance in Toba Lake area. The method in this study is a survey method with qualitative analysis. It showed the increasing of tourism standardization related to the tourists needs, especially for Muslim. It is concluded that tourism development oriented to GTG must have policies as directions and actions to realize the goals to be achieved; including Muslim-friendly tourism.